Dopant size effects on novel functionalities: High-temperature interfacial superconductivity - Y. Eren Suyolcu (Nature Portfolio, 2017)
Abstract Among the range of complex interactions, especially at the interfaces of epitaxial oxide systems, contributing to the occurrence of intriguing effects, a predominant role is played by the local structural parameters. In this study, oxide molecular beam epitaxy grown lanthanum cuprate-based bilayers (consisting of a metallic (M) and an insulating phase (I)), in which high-temperature superconductivity arises as a consequence of interface effects, are considered. With the aim of assessing the role of the dopant size on local crystal structure and chemistry, and on the interface functionalities, different dopants (Ca2+, Sr2+ and, Ba2+) are employed in the M-phase, and the M–I bilayers are investigated by complementary techniques, including spherical-aberration-corrected scanning transmission electron microscopy. A series of exciting outcomes are found: (i) the average out-of-plane lattice parameter of the bilayers is linearly dependent on the dopant ion size, (ii) each dopant redistributes at the interface with a characteristic diffusion length, and (iii) the superconductivity properties are highly dependent on the dopant of choice. Hence, this study highlights the profound impact of the dopant size and related interface chemistry on the functionalities of superconducting oxide systems.